Balancing intersectoral demands in basin-scale planning: the case of Nepal’s western river basins - Pakhtigian, E.L.; Jeuland, M.; Dhaubanjar, Sanita; Pandey, Vishnu Prasad (Elsevier, 2020)
Basin-wide planning requires tools and strategies that allow comparison of alternative pathways and priorities at relevant spatial and temporal scales. In this paper, we apply a hydroeconomic model–the Western Nepal Energy Water Model–that better accounts for feedbacks between water and energy markets, to optimize water allocations across energy, agriculture, municipal, and environmental sectors. The model maximizes total economic benefits, accounting for trade-offs both within and across sectors. In Western Nepal, we find that surface water availability is generally sufficient to meet existing and growing demands in energy and agricultural sectors; however, expansion of water storage and irrigation infrastructure may limit environmental flows below levels needed to maintain the full integrity of important aquatic ecosystems. We also find substantial trade-offs between irrigation in Nepal and satisfaction of the institutional requirements implied by international water-use agreements with the downstream riparian India. Similar trade-offs do not exist with hydropower, however. Model results and allocations are sensitive to future domestic and international energy demands and valuations.